2018
DOI: 10.5213/inj.1836092.046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Early Recovery of Stress Urinary Incontinence Following Holmium Laser Enucleation of the Prostate in Patients With Benign Prostatic Enlargement

Abstract: PurposeTo investigate factors associated with early recovery of stress urinary incontinence (SUI) following holmium laser enucleation of the prostate (HoLEP) in patients with benign prostatic enlargement (BPE).MethodsThe medical records of 393 patients who underwent HoLEP for BPE were retrospectively reviewed. Patients with SUI following HoLEP were selected and divided into 2 groups: those who experienced early recovery of SUI and those who experienced persistent SUI. Recovery of SUI within 1 month after HoLEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…For HoLEP, transient incontinence occurs in approximately 22% of cases. According to Cho et al [26], 18 patients, 4.6% of 393 patients who underwent HoLEP experienced urinary incontinence for longer than 3 months. The factors involved in urinary incontinence were transition zone prostate volume and the enucleation ratio.…”
Section: Discussionmentioning
confidence: 99%
“…For HoLEP, transient incontinence occurs in approximately 22% of cases. According to Cho et al [26], 18 patients, 4.6% of 393 patients who underwent HoLEP experienced urinary incontinence for longer than 3 months. The factors involved in urinary incontinence were transition zone prostate volume and the enucleation ratio.…”
Section: Discussionmentioning
confidence: 99%
“…44,50,51 Diabetes mellitus, longer operation and enucleation time, surgeon's experience, larger prostate size, higher blood loss are some factors associated with SUI after HoLEP. [52][53][54] Furthermore, the resection of tissue near the external sphincter might result in temporary UI. [52][53][54] The modified bilobar approach of HoLEP decreased the incidence of retrograde ejaculation and UI, improving the patients' quality of life after surgery compared to the traditional three-lobe technology.…”
Section: Post-holep Urinary Incontinencementioning
confidence: 99%
“…[52][53][54] Furthermore, the resection of tissue near the external sphincter might result in temporary UI. [52][53][54] The modified bilobar approach of HoLEP decreased the incidence of retrograde ejaculation and UI, improving the patients' quality of life after surgery compared to the traditional three-lobe technology. 19 Multivariate analysis revealed that the prostate transition zone volume was significantly associated with the early recovery of SUI.…”
Section: Post-holep Urinary Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the current issue of INJ contains clinical studies to offer useful information about specific treatment modalities, such as an analysis of risk factors for stress UI after holmium laser enucleation of the prostate [7], follow-up results of a new therapeutic device for anterior vaginal wall prolapse [8], and factors associated with successful sacral neuromodulation [9].…”
mentioning
confidence: 99%